THUR 007 A garden variety neuropathy. Issue 10 (13th September 2018) - Sumangala, Salini; Simpson, Ben; George, Jithin
Abstract : A 47 year old with subacute onset of walking difficulties, asymmetric lower limb and facial weakness and areflexia was admitted as a suspected case of Guillain-Barre syndrome. Clinical examination revealed left lower motor neuron facial weakness, right upper limb and lower limb weakness and a suspended area of pain and allodynia at T7. Structural imaging of the brain and spine was normal. CSF protein was elevated with pleocytosis. Nerve conduction studies was suggestive of proximal demyelinating polyradicular neuropathy. The clinical suspicion of neuroborreliosis was confirmed in CSF with Borrelia VlsE antigen positivity and serum Borrelia Burgdorferi IgG EIA positivity. The patient had no recollection of tick exposure but did recall a presumed horsefly bite on the forearm two weeks earlier of uncertain significance. This is a case of Bannwarth syndrome - meningoradiculoneuritis due to neuroborreliosis endemic in Northern Europe. Our patient was treated with Ceftriaxone with rapid improvement of symptoms. This case highlights the importance of careful history taking including ascertainment of travel to Borrelia endemic areas and recognition of this eminently treatable meningoradiculoneuropathy.